Democracy and Civil Society in Asia: Volume 1; Globalization, Democracy and Civil Society in Asia - Fahimul Quadir (Palgrave, 2004)
This edited volume brings together a number of well-known scholars and activists from various parts of the world to present critical perspectives on recent and long term trends in the economic, socio-cultural and political life of the people of Asia and examines the policies and constraints faced by the nation-states of the region. It contributes to and enriches the current debates on globalization, the prospects for democracy, and sustainable human development. The book offers an incisive assessment of the role of civil society in creating a democratic political culture in Asia.